Effects of corn stalk fiber content on properties of biomass brick. (30th November 2016) - Lu, Zeguang; Zhao, Ziyue; Wang, Meng; Jia, Wanda
Highlights: Piling density is increasing with the increasing corn stalk fiber content. Elastic recovery and drying shrinkage and permanent deformation rates in thickness are the greatest. Compression strength is changing from low to high similar to a concave parabola. Abstract: In order to explore the effects of corn stalk fiber content on properties of biomass brick, compression strength and deformation rate are studied. Compression strength ranges similar to a concave parabola with the increasing corn stalk fiber content. Deformation rates in thickness are greater than ones in length and width. Drying shrinkage and permanent deformation rates of brick are greater than elastic recovery one in length and width. Elastic recovery deformation rate is greater than drying shrinkage and permanent ones in thickness. The results provide a basic theory for manufacturing biomass brick.